Disciplinary techniques : perception of the teachers in three private schools in Kuala Lumpur and Selangor - Buh, Mohamed Farah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1998)
The main purpose of this study is to investigate the perception of teachers of three private schools in K.L and Selangor regarding the effectiveness of three disciplinary techniques namely: prevention, positive reinforcement (rewards) and punishment. It also attempts to identify the misbehavioural problems of pupils in the classroom setting. The instrument for data collection was a self-constructed questionnaire. Descriptive statisticswere applied for data analysis. The teachers' responses were rated on a five-point Likert scale. 109 teachers participated in the study, 35 were male and 74 were female, from three schools namely: "Sekolah Seri Utama", "Sekolah Islam Al-Amin" and"Sekolah Kiblah". Ther findings indicate that "playing during work time", "not paying attention" and "talking out of turn" are the most prevalent and serious problems in the clasroom. The results also show that positive reinforcement followed by prevention are the most frequently used techniques. Prevention is shown to be more effective than positive reinforcement, whereas punishment is clearly the least frequent and the least effective technique of all. Furthemore, the results reveal that the preceptions of male and female respondensts concerning the effectiveness of the 23 techniques were relatively close. However, the responses of teachers with different qualification-Bachelor degree holders, and those holding a Certificate or a Diploma in Education, were very different. The responses of teachers also differed according to their teaching experience.